Booklet on sport fishing in Barcelos, Amazonas, Brazil user's views - Lubich, Chiara (Brasil, 2024)
The incredible beauty of the middle Negro River region in the Amazon,represented in the municipality of Barcelos, Amazonas, attracts many people wholove sport fishing. The black waters of paradisiacal settings and the uniquediversity of plants and animals are so special that not only the fishers, but alsoother people interested in nature visit the region.This booklet highlights the importance of sport fishing tourism in the middleNegro River basin and presents results obtained in the doctoral research entitled"Sport Fishing in the Middle Negro River Basin, Amazonas, Brazil: Ecological,Economic and Social Assessment", developed by Chiara Lubich under theguidance of professors Carlos Freitas and Flávia Souza of the Federal University ofAmazonas.As the focal topic of the research, sport fishing tourism plays a crucial role inpromoting the conservation of natural resources and stimulating the localeconomy. In addition to providing unique experiences to sport fishers, the activitygenerates jobs for guides, traders, business people and other communitymembers. Through this study, it was possible to understand the impact of thisactivity from different perspectives, which generated important information thatcontributes to the knowledge of the activity carried out in the state of Amazonas,Brazil.